Essays in the History of Medicine - Lei Xu (Wolters Kluwer Health/LWW, 2019)
Professor Karl Sudhoff had spent most of his career time researching the history of medical development in medieval Europe. The book collects the source fragment of the evidence of Professor Sudhoff's job.